Determinants of fast attack performance on match outcome in the elite women`s ice hockey - Tian, N.; Xu, G. (PLOS ONE, 2024)
The primary objective of this study was to discern the determinants affecting the ice hockey game based on the performance of the fast attack between the winning and losing teams. Data from the women`s ice hockey games at the Beijing 2022 Winter Olympics (n = 28) were used. A total of 2011 fast attacks were recorded, which included winning team 1156 times and losing team 855 times. 29 variables from nine categories were involved and analysed using chi-square tests, univariate tests and binary logistic regression. As a result, that fast attack performance varies between winning and losing teams, Effective Offensive Play. Scoring Analysis of the 2005 World Championships and the 2006 Olympics, INT, DZ, OZ, one-timer, dekes, shooting zone 1, shooting zone 3, shooting zone 4, SOG, SG%, 2nd period, PK, are key variables in distinguishing the winner and loser (P<0.05). The predictive model shows that shooting zone 4 (OR = 0.824), one-timer (OR = 1.255), 2nd period (OR = 1.193), SOG (OR = 1.230), and SG% (OR = 1.170) are determining factors of game outcomes. The current information has important practical applications as it allows coaches and players to improve the tactical strategy and offensive efficiency of the game.